2008
DOI: 10.1104/pp.108.119842
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lipid (DOPG) Vesicles Accumulate in the Cell Plate Region But Do Not Fuse    

Abstract: The cell plate is the new cell wall, with bordering plasma membrane, that is formed between two daughter cells in plants, and it is formed by fusion of vesicles (approximately 60 nm). To start to determine physical properties of cell plate forming vesicles for their transport through the phragmoplast, and fusion with each other, we microinjected fluorescent synthetic lipid vesicles that were made of 1,2-dioleoyl-sn-glycero-3-[phospho-rac-(1-glycerol)] (DOPG) into Tradescantia virginiana stamen hair cells. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The vesicles initially fuse to each other and then to the growing reticulate structure to deliver their content to the developing tubulovesicular network. The actin filaments form two opposing sets that are oriented parallel to the microtubules, connecting the phragmoplast to the parental cell cortex and restraining the accumulation and fusion of vesicles to the midzone of the cell plate 103,104 . Using tobacco BY-2 cell culture lines and Arabidopsis root epidermal cells, van Oostende-Triplet et al 105 showed that cell-plate development entails three distinct phases: an initial plate assembly phase is followed by primary and secondary centrifugal growth stages.…”
Section: Cell Plate Formationmentioning
confidence: 99%
“…The vesicles initially fuse to each other and then to the growing reticulate structure to deliver their content to the developing tubulovesicular network. The actin filaments form two opposing sets that are oriented parallel to the microtubules, connecting the phragmoplast to the parental cell cortex and restraining the accumulation and fusion of vesicles to the midzone of the cell plate 103,104 . Using tobacco BY-2 cell culture lines and Arabidopsis root epidermal cells, van Oostende-Triplet et al 105 showed that cell-plate development entails three distinct phases: an initial plate assembly phase is followed by primary and secondary centrifugal growth stages.…”
Section: Cell Plate Formationmentioning
confidence: 99%
“…This assumption is further supported by the finding that BDM (a myosin ATPase inhibitor) caused inhibition of cell plate late lateral expansion in Tradescantia stamen hair cells [8] . On the other hand, the results obtained by microinjection of synthetic fluorescent lipophilic vesicles suggest that MFs may have a role in the transport of vesicles towards the cell plate [23] . Our present results are consistent to these observations, however, an alternative mechanism might exist for the vesicle transport through the actin cytoskeleton.…”
Section: Dynamics Of the Actin Cytoskeleton Plays Important Roles In mentioning
confidence: 97%
“…Generally, the phragmoplast is a cytoplasmic dense area in the spindle containing microtubules, actin filaments, endoplasmic reticulum (ER), and cell plate forming vesicles and forms in anaphase during common somatic division (Staehelin and Hepler 1996, Seguí-Simarro et al 2004, Jürgens 2005. However, in median plane of the tobacco BY-2 suspension cell at late telophase, microtubules are absent from the central part of the phragmoplast (Esseling-Ozdoba et al 2008). Shamina et al (2007) studied cytoskeletal rearrangements during meiotic anaphase in a number of monocotyledonous plant species and found that central spindle fibers that move centrifugally, along with newly-formed MTs, were the basis of phragmoplast formation and function in MMCs of monocotyledonous plant species with successive cytokinesis stages.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%